Randomized Control Trial for Reduction of Body Weight, Body Fat Patterning, and Cardiometabolic Risk Factors in Overweight Worksite Employees in Delhi, India - Usha Shrivastava; Mahrukh Fatma; Smriti Mohan; Padam Singh; Anoop Misra (Journal of Diabetes Research)
Background. We studied the impact of the multicomponent interventions on body weight and cardiometabolic risk factors in overweight individuals working in corporate worksites. Methods. Overweight (BMI ≥ 23 kg/m2) subjects were recruited from four randomised worksites [two active intervention (n, recruited, 180, completed 156) and two control (n, recruited 130, completed 111)]. Intensive intervention was given at intervention worksite. Results. High prevalence (%) of obesity (90.9, 80.2), abdominal obesity (93.5, 84.3), excess skinfold thickness (70.3, 75.9), and low high-density lipoprotein cholesterol (HDL-c) levels (56.8, 63.7) were seen in the intervention and the control group, respectively. At the end of intervention, the following significant changes were observed in the intervention group: decrease in weight, BMI, waist circumference, serum triglycerides, and increase in HDL-c. Weight loss of more than 5% was seen in 12% and 4% individuals in the intervention and control groups, respectively. Most importantly, the sum of all the skinfold measurements (mm) in the intervention group decreased significantly more than the control group (12.51 ± 10.38 versus 3.50 ± 8.18, resp.). Conclusion. This multicomponent worksite trial showed a reduction in weight, excess subcutaneous fat, and cardiometabolic risk factors after 6 months of active intervention in overweight Asian Indians. Trial Registration. This trial is registered with NCT03249610.